THE INCREASE OF SECURITY IN AUSTRIA THROUGH EDUCATION IN THE AUSTRIAN ARMED FORCES - Unger Markus (2017)
Global conflicts, crises, natural disasters are dominating the media. Nowadays the security situation with current forms of threats all over the world is a very big challenge for politic and security stake holders. Migration and terrorism are causing dangers that can only be managed via international and comprehensive measures. As a result, some states are re-arming their army with high-technologized equipment and are raising their strength. In this context, the protection of the critical infrastructure becomes more and more important. In this complex situation where systems are more and more networked, the Austrian Armed Forces (AAF) have to work together with different actors and need to be well educated and trained. Indeed military leaders are confronted with increasingly complex requirements in the field of joint command and control and will require one, compared to the current level, significantly higher proportion of military-scientific, tertiary educated military leaders. The focus of this thesis is on the education in the AAF with regards to the current and future threats. Moreover examples of a comprehensive approach in the military education together with other nations will be given.